The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.15537/smj.2023.44.1.20220772
|View full text |Cite
|
Sign up to set email alerts
|

Primary lymphoma of the kidney

Abstract: Histopathological and immunohistochemical slides were reviewed, and additional immunohistochemistry stains were carried out in selected cases. Follow-up data were also collected. Original ArticleResults: There were 17 identified cases of PRL. The age of the patients ranged from 4-76 years )median: 50.5 years and mean: 46.8 years(, 11 )64.7%( were males, and 6 )35.3%( were females. There were 12 cases of diffuse large B-cell lymphoma, 3 cases of Burkitt's lymphoma, and 2 cases of post-transplant lymphoprolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
0
0
Order By: Relevance
“…12 However, it has been shown that SOPC is beneficial for patient care and can reduce the frequency of inappropriate chemotherapy or radiotherapy. 24 Hence, health policy regarding SOs is a matter of balancing benefits and costs. 25 Identifying discrepancies retrospectively can also have implications on the quality assurance and training needs of the original pathologist.…”
Section: Discussionmentioning
confidence: 99%
“…12 However, it has been shown that SOPC is beneficial for patient care and can reduce the frequency of inappropriate chemotherapy or radiotherapy. 24 Hence, health policy regarding SOs is a matter of balancing benefits and costs. 25 Identifying discrepancies retrospectively can also have implications on the quality assurance and training needs of the original pathologist.…”
Section: Discussionmentioning
confidence: 99%